-3(2x^2-xy)-4(-6+xy+x^2)其中x,y满足(x+2)^2+丨y-3丨=0

来源:学生作业帮助网 编辑:作业帮 时间:2024/10/02 19:05:38
-3(2x^2-xy)-4(-6+xy+x^2)其中x,y满足(x+2)^2+丨y-3丨=0
x)503ҭ55Ӯ5n{cmN _l۬QmgdNJJ]c ik`TOv;%*egkJ?؂C*YikSak׃`I[]3 [(fdkRQ qFP)C>\DKCd1,c_\g K

-3(2x^2-xy)-4(-6+xy+x^2)其中x,y满足(x+2)^2+丨y-3丨=0
-3(2x^2-xy)-4(-6+xy+x^2)其中x,y满足(x+2)^2+丨y-3丨=0

-3(2x^2-xy)-4(-6+xy+x^2)其中x,y满足(x+2)^2+丨y-3丨=0
(x+2)^2+丨y-3丨=0
而(x+2)^2>=0,丨y-3丨>=0
∴丨y-3丨=0,(x+2)^2=0
y=3,x=-2
-3(2x^2-xy)-4(-6+xy+x^2)
=-6x^2+3xy+24-4xy-4x^2
=-10x^2-xy+24
=-10*(-2)^2-3*(-2)+24
=-10